A Retrospective Study of Insulin and Insulin Analogues in Type I and Type II Diabetic Patients - C, Dhandapani; K, Greeshma; A, Vijay K; G, Arul Kumran K S (Indian Journal of Pharmacy Practice)
Study was carried out to compare and estimate the safety, efficacy and quality of life of insulin and insulin analogue in Type I and Type II Diabetic patients. A retrospective observational study was conducted on 50 patients in which 30 patients were on conventional insulin and 20 patients on analogues. Safety was measured based on number of hypoglycemic events and the efficacy by comparing FBS and HbA c levels in both groups. QoL was assessed by using EQ-5D 1 questionnaire and EQ Visual Analogue Scale (EQ-VAS). Percentage of hypoglycemic events in conventional insulin group was 53.3% (n=16) and 20% (n=4) in analogue group. Risk of hypoglycemia has been estimated by using Fisher's exact Test (p=0.02). The mean value of FBS for conventional insulin and insulin analogue subjects was 176.85 ± 1.58 and 162.36±2.01 respectively whereas the mean value of HbA1c was found to be 8.72 ± 0.04 and 8.67 ± 0.07 respectively. The percentage of patients reported 'no problem' was considered as they have better quality of life. Analogues have low risk of hypoglycemia as number of hypoglycemic events are reduced in those patients but these benefits are not reliable across insulin types. For glycaemic control, analogues and conventional insulins do not constitute statistically vital differences. And there was no significant impact of treatment in diabetic patients even though analogue group reported better QoL. Out of all dimensions majority of them are anxious and depressed among the study population.
Keywords: Insulin analogs; hypoglycemia; efficacy; safety; quality of life